2022
DOI: 10.48550/arxiv.2204.09001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$W$-Boson Mass Anomaly from Scale Invariant 2HDM

Abstract: The recently reported measurement of the W -boson mass by CDF-II collaboration is significantly heavier than that of the Standard Model prediction. We study this anomaly in the scale invariant Two-Higgs-Doublet-Model (2HDM) with a Z2 symmetry to avoid the flavor-changing-neutralcurrent (FCNC). In this scenario the Higgs particle is the classically massless scalon in the scale invariant 2HDM gaining its mass by radiative corrections, hence being naturally light. Moreover, because of the scale symmetry the model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In the present paper, we will discuss the implications of the new CDF measurement on the Two-Higgs Doublet Model (2HDM) which predicts in its spectrum 2 CP-even, h and H (with M h < M H ), one CP-odd A and a pair of charged Higgs H ± . Recently, there have been several studies addressing a similar issue within: the 2HDM [7][8][9][10][11][12][13][14][15][16]57], triplet extension [18][19][20] and also other SM extensions . In the present study, we identify the observed SM Higgs with H which properties are consistent with the LHC measurements and assume that the second CP-even Higgs is lighter than 125 GeV.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we will discuss the implications of the new CDF measurement on the Two-Higgs Doublet Model (2HDM) which predicts in its spectrum 2 CP-even, h and H (with M h < M H ), one CP-odd A and a pair of charged Higgs H ± . Recently, there have been several studies addressing a similar issue within: the 2HDM [7][8][9][10][11][12][13][14][15][16]57], triplet extension [18][19][20] and also other SM extensions . In the present study, we identify the observed SM Higgs with H which properties are consistent with the LHC measurements and assume that the second CP-even Higgs is lighter than 125 GeV.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the announcement of the W -mass has spurred a series of investigations, each invoking some NP scenario, some of the earliest ones being [21][22][23][24][25][26][27]. Further speculations in this direction have included, for instance, supersymmetric models [28][29][30][31][32][33], non-supersymmetric extended Higgs sectors [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], vector-like fermions [52][53][54][55][56],…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it suggests that the precision electroweak parameter T [78,79] lies in the range 0.1 − 0.3, the precise value depending on the treatment of other experimental input and on the assumptions made about the combination with other precision parameters [80][81][82][83][84][85][86][87][88][89][90]. Several studies suggest that 2HDMs can accommodate these values [91][92][93][94][95][96][97][98][99].…”
Section: Introductionmentioning
confidence: 99%